PERCEPTION OF BUSINESS ENGLISH COMMUNICATION STUDENTS’ TOWARDS THE DUOLINGO APPLICATION AS A MEDIUM FOR LEARNING ENGLISH VOCABULARY - Nurul Aulia; Riny Jefri; Andi Hajar (International Journal of Business English and Communication, 2026)
The purpose of this study was to determine the perceptions of Business English Communication students towards Duolingo as a medium for learning English vocabulary. This research uses a descriptive quantitative method, with a sample of 23 Business English Communication students. This study used questionnaires and interviews as data collection tools. The results of this study show that students' perceptions of Duolingo are very positive, in its use students agree that Duolingo is easy, effective, and interesting to use as a medium for learning English vocabulary. In addition, the use of Duolingo also proved to have a positive impact on their learning.